Impact of the interval between neoadjuvant immunochemotherapy and surgery on surgical–pathological outcomes in non-small cell lung cancer - Chen, Jiawei; Deng, Hongsheng; He, Jiaxi; Wang, Zhufeng; Li, Shuben (Frontiers in Oncology, 2022)
Introduction The interval between neoadjuvant immunochemotherapy and surgery in patients with non-small cell lung cancer (NSCLC) has not been well characterized. This study investigated the association between the time-to-surgery (TTS) interval and surgical-pathological outcomes. Method Clinical data of patients who received neoadjuvant immunochemotherapy followed by surgery for NSCLC between January 2019 and September 2021 were collected. The patients were divided into three groups based on TTS interval: the early-surgery group (ESG), the standard-surgery group (SSG), and the delayed-surgery group (DSG). The primary outcomes were objective response rate (ORR), major pathological response (MPR), and pathological complete response (pCR). The secondary end-point was surgical outcomes. Results Of the 171 patients, 16 (9.4%) received surgery ≤28 days, 49 (28.7%) received surgery between 29-42 days, and 106 (61.9%) received surgery ≥ 43 days after neoadjuvant immunochemotherapy, with a media TTS of 46 days. The postoperative drainage of the ESG group (455.1ml) was significantly less than the SSG group (680.7ml) or the DSG group (846.5ml) (p=0.037). However, the TTS interval did not influence the operation time, intraoperative bleeding, and postoperative hospital stays (p = 0.54, 0.60, 0.17). ORR was observed in 69%, 51%, 56% (p=0.46). The MPR was 50%, 47%, 58% (p=0.38). Similarly, no statistically significant difference was shown in pCR (31%, 27%, 42%, p=0.14) Conclusion This retrospective study indicated that TTS shows no significant effect on the feasibility and safety of surgery in the neoadjuvant immunochemotherapy setting. Although not statistically significant, longer TTS showed a trend that delayed surgery was associated with pathological response.